2016
DOI: 10.1111/eva.12345
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of lodgepole pine and interior spruce to climate: implications for reforestation in a warming world

Abstract: We investigated adaptation to climate in populations of two widespread tree species across a range of contrasting environments in western Canada. In a series of common garden experiments, bud phenology, cold hardiness, and seedling growth traits were assessed for 254 populations in the interior spruce complex (Picea glauca, P. engelmannii, and their hybrids) and for 281 populations of lodgepole pine (Pinus contorta). Complex multitrait adaptations to different ecological regions such as boreal, montane, coasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 40 publications
5
67
0
Order By: Relevance
“…Possible introgression with Engelmann spruce, native to higher elevation than white spruce, would enhance its adaptation to these mountainous conditions at the cost of lower growth (De La Torre, Wang, Jaquish, & Aitken, ). Liepe, Hamann, Smets, Fitzpatrick, and Aitken () also reported that high‐elevation sources of spruce had short growing seasons, lacked strong cold tolerance, and tended to be poor growers. The other six provenances in our study showed a clear trade‐off between growth and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Possible introgression with Engelmann spruce, native to higher elevation than white spruce, would enhance its adaptation to these mountainous conditions at the cost of lower growth (De La Torre, Wang, Jaquish, & Aitken, ). Liepe, Hamann, Smets, Fitzpatrick, and Aitken () also reported that high‐elevation sources of spruce had short growing seasons, lacked strong cold tolerance, and tended to be poor growers. The other six provenances in our study showed a clear trade‐off between growth and survival.…”
Section: Discussionmentioning
confidence: 99%
“…, Liepe et al. ). At the same time, North American tree species exhibit steep geographic clines that are associated with variable responses to extreme environmental conditions, such as drought and frost, across populations (Rehfeldt et al.…”
Section: Synthesis and Conclusionmentioning
confidence: 99%
“…Local adaptation of populations to unique, local climates may generate variable climate change responses across a species' range, and recent evidence suggests that locally adapted traits may not be tightly correlated with temperature gradients (Liepe et al. ), adding an additional element of uncertainty to expected species responses. We do not dedicate significant consideration to genetic adaptation in this review, as a thorough review of the issue is provided elsewhere (Aitken et al.…”
Section: Synthesis and Conclusionmentioning
confidence: 99%
“…Certainly high levels of such gene flow have been noted among remnant eucalypt populations in highly fragmented landscapes in Western Australia (Sampson & Byrne 2008;Byrne et al 2008). Additionally, recent empirical studies showing possible cryptic adaptation to soil-types along climate gradients , and non-linear relationships between trait responses and climate variables (Liepe et al 2016), highlight that generalisations about the adaptive potential of populations based soley on climatic factors can be misleading, and could even result in translocations being maladaptive.…”
Section: Future Issuesmentioning
confidence: 99%
“…However, the consequences of exotic gene flow may need to be re-assessed in the light of global climate change in order to recognise the goals of assisted gene flow and other adaptation strategies. A change in conservation priorities towards assisted gene flow may or may not become a reality in Australia, although it is already underway in British Columbia (Liepe et al 2016) and the expansion of this Canadian model to temperate forests globally has been strongly advocated (Aitken & Bemmels 2016). If assisted gene flow is implemented in Australia, then the consequences of gene flow from plantation forestry, whether it be inter-or intra-specific gene flow, would require re-evaluation.…”
Section: Future Issuesmentioning
confidence: 99%